THE EFFECT OF ORGANIZATIONAL JUSTICE ON TURNOVER INTENTIONS: A FIELD STUDY IN GAZIANTEP - ASLAN, Huseyin; Ucar, Mustafa (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The aim of this study is to determine employee perception of organizational justice which is an indicative of employee turnover intentions. In accordance with this purpose, 150 questionnaires were conducted with the employees of 3-4 and 5 star hotels still operating in Gaziantep. Analyses show that, there is a significant and negative correlation between organizational justice and employee turnover intentions. Results indicate that factors of organizational justice reduce the rate of employees turnover intentions.